Lead-barium titanate-based thermal sensitive ceramic coated with sintering aid and preparation method of lead-barium titanate-based thermal sensitive ceramic

By using a core-shell structure design with a sintering additive coated on the lead barium titanate-based thermosensitive ceramic, the problem of power attenuation and voltage breakdown after long-term power-on is solved, and the high voltage withstandability and stability of the ceramic is achieved.

CN119874354APending Publication Date: 2025-04-25HAINING YONGLI ELECTRONICS CERAMICS

Patent Information

Application Number
CN202510065663.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing barium titanate-based thermistor ceramics have severe power attenuation after long-term power-on, and have potential voltage breakdown risks, making it difficult to effectively adjust their room temperature resistivity, lift-resistance ratio and voltage resistance performance.

Method used

The lead barium titanate-based thermosensitive ceramic is coated with a sintering aid. Through the design of the core-shell structure, the ceramic grains are refined and densification is promoted, thereby improving the voltage resistance of the ceramic.

Benefits of technology

On the basis of maintaining excellent PTC effect, the voltage withstandability of ceramics is effectively improved, and its stability and breakdown resistance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874354A_ABST
    Figure CN119874354A_ABST
Patent Text Reader

Abstract

The invention discloses a sintering aid coated lead barium titanate-based thermal sensitive ceramic and a preparation method thereof, and relates to the technical field of material science, the raw materials of the core layer comprise barium carbonate, lead tetraoxide, calcium carbonate, strontium carbonate, zirconium oxide, tin oxide, titanium dioxide, manganese oxide and niobium pentoxide; the raw materials of the shell layer comprise silica sol, an aluminum compound, a calcium compound, a sodium compound, a potassium compound, a magnesium compound and boric acid; the preparation method comprises the following steps: mixing the raw materials of the core layer, calcining at 950-1050 DEG C, adding a deionized water solution of the raw materials of the shell layer, mixing, calcining at 1000-1100 DEG C, adding a polyvinyl alcohol water solution, granulating, forming, degumming and sintering to obtain the sintering aid coated lead barium titanate based thermal sensitive ceramic. According to the invention, the sintering aid is used for coating the lead barium titanate-based thermal sensitive ceramic, so that the densification of the ceramic is promoted while grains are refined, and the ceramic has high voltage resistance and excellent PTC (Positive Temperature Coefficient) effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science and technology, and in particular relates to a sintering aid-coated barium lead titanate-based thermal sensitive ceramic and a preparation method thereof. Background Art

[0002] BaTiO3 ceramic is a representative ferroelectric material. Its lattice structure is a typical perovskite structure. Pure barium titanate material is a good insulating material. Its resistivity exceeds 10 at room temperature. 12 Ω·cm, relative dielectric constant is 10 4 , is an important type of functional ceramic material. The PTC (positive temperature coefficient) effect of BaTiO3 was first discovered by Philips of the Netherlands in the 1950s. When a trace amount of rare earth elements is introduced into BaTiO3, the ionization of the rare earth elements can lead to a higher conduction band carrier concentration, thereby increasing the conductivity of the material and becoming semiconducting, with a resistivity of 10 1 ~10 2 Ω·cm semiconductor, this kind of semiconductor is called valence controlled semiconductor, and the relationship between the resistance of the semiconductor and the temperature change showing a positive temperature coefficient is called the PTC effect.

[0003] Based on semiconductor donor doped barium titanate (BaTiO3) thermistor ceramics, which are positive temperature coefficient resistor ceramic materials, have excellent thermoelectric properties, low preparation cost, high heating efficiency, and easy regulation of its lift-to-resistance ratio and Curie temperature. After decades of development, they have been widely used in various technical application fields, such as self-regulating heating elements, overcurrent protection or temperature sensors. In recent years, with the trend of electric vehicles replacing internal combustion engine vehicles to cope with environmental pollution, PTC components have found new applications as the main heating equipment for electric vehicles. However, this new application field requires different and customized performance characteristics. Since heating elements account for a major part of energy consumption, the most prominent problem of the components in current applications is that long-term power-on will cause serious power attenuation of the ceramic components and there are some hidden dangers of voltage breakdown. Therefore, it is necessary to effectively adjust the room temperature resistivity, lift-to-resistance ratio and voltage resistance of PTC.

[0004] In order to optimize the PTC performance of barium titanate-based PTC ceramics and improve the stability of ceramic materials, domestic and foreign scholars have devoted themselves to studying the improvement of the performance of barium titanate-based PTC ceramics by doping and sintering processes. Cheng et al. prepared a PTC ceramic with a room temperature resistance of only 0.14Ω and a lift-to-resistance ratio of more than 10 by doping Nb into BaTiO3 and changing the sintering process. 3Low room temperature resistance PTC ceramics; Li Yanyan et al. studied the effect of different donor Nb doping amounts on the performance of barium titanate-based ceramic materials. The experiment found that with the increase of Nb2O5 doping amount, the room temperature resistance of the ceramic first decreased and then increased. When the donor Nb doping amount was 0.5mol%, its room temperature resistivity was the smallest; Zhiyu et al. studied the relationship between the semiconductivity and its sintering process, lead vacancies, barium vacancies and donor and acceptor impurities in (Ba, Pb)TiO3-based high temperature PTC semiconductor ceramics, and focused on analyzing the effect of introducing acceptor impurities Mn on the semiconductivity of the material. Ding et al. prepared a material with a room temperature resistance of only 14Ω and a rise-to-resistance ratio of 10 by changing the Mn content and continuously improving the sintering temperature and holding time. 5 , a high-performance PTC effect ceramic with a temperature coefficient of about 22%. Zhong Zhiyong used a two-step synthesis method to introduce liquid phase additives (Al2O3-SiO2-TiO2) to increase the density of the ceramic material. The prepared PTC ceramic has a breakdown voltage of more than 900V and a lift-to-drag ratio of 10 3 above.

[0005] Although barium titanate-based thermistor ceramics have been widely reported, according to current research, when ceramics are doped with low concentrations of liquid phase additives and sintering aids, the density of the ceramics is poor and the voltage resistance performance is insufficient. Although studies have found that the voltage resistance performance of ceramics can be enhanced by increasing the concentration of liquid phase additives and adding higher concentrations of sintering aids, related studies have shown that the increase in the concentration of liquid phase additives inside the ceramics will cause the resistivity of the ceramics to increase, affecting the semiconducting process of the ceramics and the PTC effect. Therefore, under the premise of maintaining the good PTC effect of barium titanate-based thermistor ceramics, improving the voltage resistance performance of the ceramics while maintaining good sintering performance is the key to the wider application of barium titanate-based thermistor ceramics. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a sintering aid coated barium lead titanate-based thermistor ceramic and a preparation method thereof, which promotes the densification of the ceramic while refining the ceramic grains, thereby effectively improving the voltage resistance of the ceramic while maintaining the excellent PTC effect of the ceramic.

[0007] To achieve the above object, the present invention provides the following technical solution: a sintering aid coated barium lead titanate-based thermistor ceramic, characterized in that it has a core-shell structure; the raw materials of the core layer are arranged in molar proportions as follows: barium carbonate accounts for 29 to 46 parts, lead tetroxide accounts for 2 to 7 parts, calcium carbonate accounts for 0.1 to 3 parts, strontium carbonate accounts for 0.1 to 4 parts, zirconium oxide accounts for 0.1 to 5 parts, tin oxide accounts for 0.1 to 8 parts, and titanium dioxide accounts for 49.4 to 49.93 parts, Manganese oxide accounts for 0.02-0.3 parts, niobium pentoxide accounts for 0.05-0.3 parts; the molar proportion array of the raw materials of its shell layer is: silica sol accounts for 0.05-0.1 parts, aluminum compounds account for 0.01-0.2 parts, calcium compounds account for 0.01-0.2 parts, sodium compounds account for 0.05-0.5 parts, potassium compounds account for 0.05-0.5 parts, boric acid accounts for 0.01-0.5 parts, and magnesium compounds account for 0.01-0.2 parts.

[0008] As a preferred embodiment, the aluminum compound is one or more of aluminum nitrate, aluminum chloride, and aluminum acetate, the calcium compound is one or more of calcium nitrate, calcium chloride, and calcium acetate, the sodium compound is one or more of sodium nitrate, sodium chloride, and sodium acetate, the potassium compound is one or more of potassium nitrate, potassium chloride, and potassium acetate, and the magnesium compound is one or more of magnesium nitrate, magnesium chloride, and magnesium acetate.

[0009] A method for preparing the sintering aid coated barium lead titanate-based thermistor ceramic as described above comprises the following steps:

[0010] (1) according to the ratio of the core layer raw materials, a certain amount of barium carbonate, lead tetroxide, calcium carbonate, strontium carbonate, zirconium oxide, tin oxide, titanium dioxide, manganese oxide, and niobium pentoxide are weighed, and then the above substances and anhydrous ethanol are placed in a ceramic ball mill, and zirconium oxide grinding balls are added for ball milling, and the ball-milled slurry is placed in an oven at 80° C. to dry for 4 to 6 hours, and then placed in an alumina crucible and kept at 950 to 1050° C. for 2 to 4 hours, and then cooled to obtain barium lead titanate-based powder;

[0011] (2) weighing a certain amount of silica sol, aluminum compound, calcium compound, sodium compound, potassium compound, boric acid, and magnesium compound according to the ratio of the shell raw materials, and then dissolving the above compounds in deionized water to obtain a 0.5-3 mol / L deionized water solution;

[0012] (3) placing the barium lead titanate-based powder prepared in the above step (1) and the deionized water solution prepared in the step (2) in a ball mill for ball milling, and then spray drying; placing the spray-dried powder in an alumina crucible, and calcining it at 1000-1100° C. for 3-6 hours;

[0013] (4) placing the calcined powder into a ball mill, adding a 5% polyvinyl alcohol aqueous solution in an amount twice the mass of the powder, ball milling and mixing, and spray granulating to obtain granulated powder;

[0014] (5) The granulated powder is dry-pressed and then kept at 300-500° C. for 4-10 hours for debinding, and then the temperature is raised to 1250-1350° C. and kept at this temperature for 2-4 hours for sintering to obtain the sintering aid-coated barium lead titanate-based thermistor ceramic of the present invention.

[0015] Beneficial effects of the present invention: Through the core-shell structure prepared by the present invention with the lead barium titanate-based powder as the core and the sintering aid precursor as the shell, the sintering aid precursor can be uniformly coated on the surface of the lead barium titanate-based powder, and the elements Ca, Sr, Zr, Sn and the like added to the lead barium titanate-based powder are used to refine the grains. At the same time, the sintering aid of the shell layer is used to refine the ceramic grains and promote the densification of the ceramic, thereby effectively improving the voltage resistance performance of the ceramic while maintaining the excellent PTC effect of the ceramic. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope image of the lead barium titanate-based thermistor ceramic prepared in the present invention. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Embodiment 1:

[0019] According to the molar ratio, 37 parts of barium carbonate, 6 parts of lead tetroxide, 1 part of calcium carbonate, 1 part of strontium carbonate, 1 part of zirconium oxide, 4 parts of tin oxide, 49.65 parts of titanium dioxide, 0.15 parts of manganese oxide and 0.2 parts of niobium pentoxide were weighed, and the above substances were placed in a ceramic ball mill together with anhydrous ethanol, and zirconium oxide grinding balls were added for ball milling. The ball-milled slurry was placed in an oven at 80°C for drying for 5 hours, and then placed in an alumina crucible for heat preservation at 1000°C for 3 hours. After cooling, barium lead titanate-based powder was obtained.

[0020] 0.5 parts of silica sol, 0.1 parts of aluminum nitrate, 0.02 parts of calcium nitrate, 0.06 parts of sodium nitrate, 0.12 parts of potassium nitrate, 0.05 parts of boric acid, and 0.05 parts of magnesium nitrate were weighed according to the molar ratio, and then dissolved in deionized water to obtain a 2 mol / L deionized water solution.

[0021] The prepared barium lead titanate powder is placed in a ball mill together with a deionized water solution for ball milling, followed by spray drying; the spray-dried powder is placed in an alumina crucible and calcined at 1050°C for 4 hours. The calcined powder is placed in a ball mill, and a 5% polyvinyl alcohol aqueous solution is added at twice the mass of the powder. After ball milling, spray granulation is performed to obtain granulated powder; the granulated powder is dry-pressed, and then kept at 400°C for 8 hours for debinding, and then heated to 1290°C for 3 hours for sintering to obtain a sintering aid-coated barium lead titanate-based thermistor ceramic.

[0022] The scanning electron microscope image of the lead barium titanate-based thermistor ceramic prepared in this example is as follows: Figure 1 shown.

[0023] The two sides of the ceramic sample were polished, coated with ohmic silver paste and kept at 550°C for 30 minutes to complete the electrode preparation; then the ceramic sample was subjected to resistance-temperature test and voltage resistance test, and its performance parameters are shown in Table 1.

[0024] Embodiment 2:

[0025] According to the molar ratio, 33.5 parts of barium carbonate, 7 parts of lead tetroxide, 3 parts of calcium carbonate, 0.5 parts of strontium carbonate, 2 parts of zirconium oxide, 4 parts of tin oxide, 49.4 parts of titanium dioxide, 0.3 parts of manganese oxide and 0.3 parts of niobium pentoxide were weighed, and the above substances were placed in a ceramic ball mill together with anhydrous ethanol, and zirconium oxide grinding balls were added for ball milling. The ball-milled slurry was placed in an oven at 80°C for 4 hours and then placed in an alumina crucible and kept at 950°C for 4 hours. After cooling, barium lead titanate-based powder was obtained.

[0026] 1 part of silica sol, 0.2 parts of aluminum nitrate, 0.2 parts of calcium nitrate, 0.1 parts of sodium nitrate, 0.3 parts of potassium nitrate, 0.2 parts of boric acid, and 0.1 parts of magnesium nitrate were weighed according to the molar ratio, and then dissolved in deionized water to obtain a 0.5 mol / L deionized water solution.

[0027] The prepared barium lead titanate powder is placed in a ball mill together with a deionized water solution for ball milling, followed by spray drying; the spray-dried powder is placed in an alumina crucible and calcined at 1000°C for 6 hours. The calcined powder is placed in a ball mill, and a 5% polyvinyl alcohol aqueous solution is added at twice the mass of the powder, and spray granulation is performed after ball milling to obtain granulated powder; the granulated powder is dry-pressed, and then kept at 500°C for 4 hours for debinding, and then heated to 1280°C for 4 hours for sintering to obtain a sintering aid-coated barium lead titanate-based thermistor ceramic.

[0028] The two sides of the ceramic sample were polished, coated with ohmic silver paste and kept at 550°C for 30 minutes to complete the electrode preparation; then the ceramic sample was subjected to resistance-temperature test and voltage resistance test, and its performance parameters are shown in Table 1.

[0029] Embodiment 3:

[0030] According to the molar ratio, 35.8 parts of barium carbonate, 5 parts of lead tetroxide, 0.1 parts of calcium carbonate, 0.1 parts of strontium carbonate, 1 part of zirconium oxide, 8 parts of tin oxide, 49.6 parts of titanium dioxide, 0.2 parts of manganese oxide and 0.2 parts of niobium pentoxide were weighed, and the above substances were placed in a ceramic ball mill together with anhydrous ethanol, and zirconium oxide grinding balls were added for ball milling. The ball-milled slurry was placed in an oven at 80°C and dried for 6 hours, and then placed in an alumina crucible and kept at 1050°C for 2 hours. After cooling, barium lead titanate-based powder was obtained.

[0031] 0.2 parts of silica sol, 0.05 parts of aluminum nitrate, 0.01 parts of calcium nitrate, 0.1 parts of sodium nitrate, 0.2 parts of potassium nitrate, 0.1 parts of boric acid, and 0.05 parts of magnesium nitrate were weighed according to the molar ratio, and then dissolved in deionized water to obtain a 3 mol / L deionized water solution.

[0032] The prepared barium lead titanate powder is placed in a ball mill together with a deionized water solution for ball milling, followed by spray drying; the spray-dried powder is placed in an alumina crucible and calcined at 1100°C for 3 hours. The calcined powder is placed in a ball mill, and a 5% polyvinyl alcohol aqueous solution is added at twice the mass of the powder, and spray granulation is performed after ball milling to obtain granulated powder; the granulated powder is dry-pressed, and then kept at 300°C for 10 hours for debinding, and then heated to 1320°C for 2 hours for sintering to obtain a sintering aid-coated barium lead titanate-based thermistor ceramic.

[0033] The two sides of the ceramic sample were polished, coated with ohmic silver paste and kept at 550°C for 30 minutes to complete the electrode preparation; then the ceramic sample was subjected to resistance-temperature test and voltage resistance test, and its performance parameters are shown in Table 1.

[0034] Table 1 Electrical properties of lead barium titanate based thermistor ceramics prepared by the present invention

[0035]

Claims

1. A sintering aid coated barium lead titanate based thermistor ceramic, characterized in that: The invention has a core-shell structure; the raw materials of the core layer are as follows: 29-46 parts of barium carbonate, 2-7 parts of lead tetroxide, 0.1-3 parts of calcium carbonate, 0.1-4 parts of strontium carbonate, 0.1-5 parts of zirconium oxide, 0.1-8 parts of tin oxide, 49.4-49.93 parts of titanium dioxide, 0.02-0.3 parts of manganese oxide, and 0.05-0.3 parts of niobium pentoxide; the raw materials of the shell layer are as follows: 0.05-1 parts of silica sol, 0.01-0.2 parts of aluminum compounds, 0.01-0.2 parts of calcium compounds, 0.05-0.5 parts of sodium compounds, 0.05-0.5 parts of potassium compounds, 0.01-0.5 parts of boric acid, and 0.01-0.2 parts of magnesium compounds.

2. The sintering aid coated barium lead titanate based thermistor ceramic according to claim 1, characterized in that: The aluminum compound is one or more of aluminum nitrate, aluminum chloride, and aluminum acetate; the calcium compound is one or more of calcium nitrate, calcium chloride, and calcium acetate; the sodium compound is one or more of sodium nitrate, sodium chloride, and sodium acetate; the potassium compound is one or more of potassium nitrate, potassium chloride, and potassium acetate; and the magnesium compound is one or more of magnesium nitrate, magnesium chloride, and magnesium acetate.

3. A method for preparing the sintering aid coated barium lead titanate-based thermistor ceramic according to claim 1, comprising the following steps: (1) according to the ratio of the core layer raw materials, a certain amount of barium carbonate, lead tetroxide, calcium carbonate, strontium carbonate, zirconium oxide, tin oxide, titanium dioxide, manganese oxide, and niobium pentoxide are weighed, and then the above substances and anhydrous ethanol are placed in a ceramic ball mill, and zirconium oxide grinding balls are added for ball milling, and the ball-milled slurry is placed in an oven at 80° C. to dry for 4 to 6 hours, and then placed in an alumina crucible and kept at 950 to 1050° C. for 2 to 4 hours, and then cooled to obtain barium lead titanate-based powder; (2) weighing a certain amount of silica sol, aluminum compound, calcium compound, sodium compound, potassium compound, boric acid, and magnesium compound according to the ratio of the shell raw materials, and then dissolving the above compounds in deionized water to obtain a 0.5-3 mol / L deionized water solution; (3) placing the barium lead titanate-based powder prepared in the above step (1) and the deionized water solution prepared in the step (2) in a ball mill for ball milling, and then spray drying; placing the spray-dried powder in an alumina crucible, and calcining it at 1000-1100° C. for 3-6 hours; (4) placing the calcined powder into a ball mill, adding a 5% polyvinyl alcohol aqueous solution at a weight fraction of 2 times the weight of the powder, ball milling and mixing, and then spray granulating to obtain granulated powder; (5) The granulated powder is dry-pressed and then kept at 300-500° C. for 4-10 hours for debinding, and then the temperature is raised to 1250-1350° C. and kept at this temperature for 2-4 hours for sintering to obtain the sintering aid-coated barium lead titanate-based thermistor ceramic of the present invention.

Citation Information

Patent Citations

  • Cold conductor material used for electronic switches consists of a finely dispersed titanate powder and a structure made up of a core of lead titanate and a shell of barium titanate, calcium titanate or strontium titanate

    DE10045394A1

  • Method of producing fine-particle multicomponent glass powders for use as a glass flow for producing layers and decorations on glass, glass ceramic or ceramic

    US5837025A

Cited By

  • Heat-resistant multilayer ceramic substrate and preparation method thereof

    CN120247536A